MODIFIKASI ALAT KEKUTAN GRIP PADA ATLET ANGKAT BERAT - Lilis Suryaningsih; Edi Purnomo; Eka Supriatna (Universitas Tanjungpura, 2022)
This study aims to modify the grip strength of heavy lifters to improve grip strength during deadlift training so that weight lifters can increase grip strength and make it easier for coaches to train. This research is a research development or Research and Development (R&D). This research was conducted in several steps, namely: potentials and problems, data collection, product design, design validation, product trials, product revisions, usage trials. Modification of the grip strength equipment in weight lifters was first validated by material experts, practice experts, 9 respondents as product trials and 12 respondents as product trials. The results of this study are suitable for use as a grip strength training tool in weight lifters. This is seen from material experts 92% and practice experts 90% as well as product trials on a scale of 58.78% and large-scale trials of 88.70%. Thus it can be said that the modification of the grip strength device in lifters is declared feasible to be used as an exercise aid.Keywords: Power Tool Modification, Grip, Weight Lifter